(untitled) (Homoeopathy for All, 2025)
Haemorrhoids, a common and often distressing condition, involve the swelling and inflammation of the veins in the rectal area. Conventional treatments primarily focus on symptom relief, such as pain management, reducing swelling, and controlling bleeding.[1] Internal Haemorrhoids, are dilated vascular structures within the rectal mucosa that often present with painless rectal bleeding, prolapse, or a sensation of incomplete evacuation. Unlike external Haemorrhoids, they may go unnoticed until bleeding or prolapse occurs. Homeopathy offers a non-invasive, holistic, and individualized approach, addressing the root cause rather than merely suppressing symptoms. According to 6th edition of organon of medicine cure as “the highest ideal of cure is rapid gentle and permanent restoration of health, or removal and annihilation of disease in its whole extended in shortest most reliable and most harmless way on easily comprehensible principle”. In aphorism 186 (5th edition) Dr Hahnemann wrote about suppressive measures (like surgical removal or tropical treatment) that can drive the disease inward, causing deeper chronic problems. [6]